Two Coefficients of the Dyson Product - Lv, Lun; Xin, Guoce; Zhou, Yue (The Electronic Journal of Combinatorics, 2008)
In this paper, the closed-form expressions for the coefficients of x_r^2x_s^2 and x_r^2x_sx_t in the Dyson product are found by applying an extension of Good’s idea. As consequences, we find several interesting Dyson style constant term identities.